Unpacking EFL textbook content: A focus on teachers’ role in the textbook-based classroom - Zhang, Xiaodong (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This theoretical paper first explores how English-as-a-foreign-language (EFL) teachers’ beliefs impact their delivery of textbook content. In response to this important pedagogical relationship, as well as the trend of de-contextualized teaching in EFL settings, this paper argues for the compatibility of systemic functional linguistics (SFL) as an intervention tool to shape teachers’ beliefs and facilitate their deconstruction of textbook content in terms of the co-play between language form (i.e., grammar/vocabulary) and meaning representations. The paper ends with pedagogical strategies for pre-service and in-service EFL teacher education, enabling teachers to conceptualize the dynamic relationship between language form and meaning embedded in textbook content and to enact contextualized instruction in textbook-based classrooms.